Steam Reforming of Biogas over CeO2-Coated Ni-Al Plate Catalysts - Quynh Thi Phuong Bui; Kim, Yongmin; Hien Thi Bich Nguyen; Nam, Suk Woo; Han, Jong Hee; Ham, Hyung Chul; Kim, Jin Young; Choi, Sun Hee; Hong, Sung-An; Yoon, Chang Won (SPRINGER, 2015)
Hydrogen production via steam reforming of a simulated biogas was achieved in a temperature range of 500-800 A degrees C over a plate-type Ni-Al catalyst. To enhance the catalytic activity of the Ni-Al catalyst, a pretreatment process involving pre-oxidation with sequential reduction was employed prior to the reforming reactions. The activated Ni-Al catalyst exhibited increased methane conversion depending on the pre-oxidation temperature. Studies using X-ray diffraction and scanning electron microscopy suggested that the catalyst surface was restructured upon pretreatment, ultimately improving the catalytic activity. To increase its catalytic stability, CeO2 was employed additionally as a structural promoter to prevent both Ni sintering and carbon deposition. The durability of the CeO2-coated Ni-Al catalyst was improved significantly, particularly upon addition of a parts per thousand yen2.8 wt% of CeO2, with ca. 75 % of CH4 conversions being achieved without deactivation over 100 h at 700 A degrees C. The influence of the pre-oxidation temperature, reforming temperature, and steam/CH4 ratio on reforming over a CeO2-Ni-Al catalyst was also elucidated. In addition, the potential roles of CeO2 in the enhancement of activity and stability were discussed. [GRAPHICS] .
Keywords: HYDROGEN-PRODUCTION; FUEL-CELLS; METHANE; OXIDE; SURFACES